Blev templet på Garizim bygget med templet i Jerusalem som forbillede? - de Hemmer Gudme, Anne Katrine (Dansk Teologisk Tidsskrift, 2015)
Was the Yahweh temple on Mount Gerizim modelled after the temple in Jerusalem? This question is important for our understanding of the sanctuary on Mount Gerizim and the people who worshipped there; if the Gerizim temple was modelled after the Jerusalem temple the argument in favour of the Gerizim cult as derived from the cult in Jerusalem is strengthened. On the other hand, if no such connection can be demonstrated convincingly one must look elsewhere for the answer to the question of Samaritan origins.The present article gives a brief introduction to the relationship between early Judaism and early Samaritanism, or rather Southern and Northern Yahwism, followed by a presentation of Mount Gerizim and the excavations that were recently carried out there. Finally I shall turn to the theory that the temple on Mount Gerizim was modelled after the Jerusalem temple, which has recently been recast by Dr Yitzhak Magen. I conclude that the archaeological remains from the Persian period sanctuary on Mount Gerizim offer no evidence that this temple was modelled on the temple in Jerusalem.